(untitled) - Kurosawa, Akira (New York, 1982)
A first rate book and a joy to read.... It's doubtful that a complete understanding of the director's artistry can be obtained without reading this book.... Also indispensable for budding directors are the addenda, in which Kurosawa lays out his beliefs on the primacy of a good script, on scriptwriting as an essential tool for directors, on directing actors, on camera placement, and on the value of steeping oneself in literature, from great novels to detective fiction.
Keywords: Kurosawa, Akira, 1910-1998,Motion picture producers and directors; Biography; Japan